ANALISA PESAN DAN MEDIA KAMPANYE POLITIK POLITISI MUDA PARTAI KEADILAN SEJAHTERA (PKS) PADA PEMILIHAN UMUM LEGISLATIF KOTA TANGERANG SELATAN DI TAHUN 2019 - Enjang Pera Irawan (MediaKom : Jurnal Ilmiah Komunikasi, 2023)
This research titled "Analysis of Messages and Campaign Media of Young Politicians from the Prosperous Justice Party (PKS) in the 2019 Legislative Elections in South Tangerang City" is motivated by the researcher's interest in the tricks and strategies of political communication employed by young politicians to gain public support. Moreover, young politicians tend to have closer connections with the younger generation, who comprise the majority of voters today, known as millennials. The research methodology employed is qualitative descriptive. The research findings indicate that the political communication messages conveyed by the legislative candidates consist of two categories: individual campaign messages and party-sourced campaign messages. The personal campaign messages from the politicians include commitments to address various community aspirations, such as issues related to social facilities (fasos) and public facilities (fasum) within the community, handling environmental issues through waste management training, health programs like smoking cessation programs and alternative therapies. On the other hand, the party campaign messages include lifelong driving licenses (SIM seumur hidup), free motorcycle taxes, protection of religious scholars (ulama), and tax exemption for those earning less than 8 million rupiahs. The campaign media utilized in this research consist of direct face-to-face campaigning by meeting constituents in their respective regions, the use of banners and banners placed and distributed in various locations, particularly those that are less frequently accessed by legislative candidates. The design of the banners and banners employs everyday language and humorous visualizations. Additionally, social media platforms were used to showcase various campaign activities and the daily lives of the legislative candidates. The use of social media is still optimal as the messages conveyed on these platforms tend to be rigid and formal, thereby reducing my engagement with constituents.